The effect of staff satisfaction in developing employee work performance and their retention moderating role of knowledge sharing (an empirical study of a Business School in Bangladesh) - Hosen, Sharif; Arshad, Mohd Mursyid; Jahan, Tanjnin; Imon, Imran Hossain; Sultana, Sadia; Ibnat, Tahsin (Research Publishing Academy, 2018)
Employees are a substantial part of the set-up of any organisation. They play a key role as the workforce provides expertise in developing value and are one of the basic resources needed in every production process. This study includes IBAIS University which making a policy to achieve a long term vision to be a “world-class institution” by 2025. It focuses on the condition of the Bangladeshi higher education industry, which from the early nineties has been competing with local public and foreign universities to provide educational services to society. As a result, it is of significant importance to maintain employee satisfaction with their commitment and involvement in supporting the effort to sustain long-term targeted achievement. This research purpose is to analyse the effect of employee satisfaction moderated by knowledge sharing towards employee work performances and retention. The participants of this study are all employees of the institution, with the data gathering techniques applied including questionnaires and multiple regression analytical methods with moderating variables. The results of this study show that employee satisfaction has a significant effect towards employee work performance and retention. On the other hand, knowledge sharing doesn’t appear to have a significant effect on employee work performance or retention.